(Salicylaldiminato)Ni(ii)-catalysts for hydrosilylation of olefins1. Issue 4 (24th April 2015) - Srinivas, Venu; Nakajima, Yumiko; Ando, Wataru; Sato, Kazuhiko; Shimada, Shigeru
<x xml:space="preserve">Abstract</x> Olefin hydrosilylation was attained at room temperature at 0.5 mol% Ni loading by using a series of (salicylaldiminato)methylnickel complexes as catalyst precursors.